1995
DOI: 10.1149/1.2044126
|View full text |Cite
|
Sign up to set email alerts
|

The Electrodeposition of Ni‐Fe‐Cr Alloys for Magnetic Thin Film Applications

Abstract: A new bath for the electrodeposition of Ni‐Fe‐Cr magnetic thin films has been developed. The bath is similar to a typical Permalloy electrodeposition bath, being modified only by the addition of 0.020M chromic chloride and 0.10M acetic acid. Deposits with up to 8 weight percent Cr were produced; the chromium content of the deposit increased with increasing current density. Current efficiencies of up to 50% were attained when at least one‐half of the chromium in the bath was present as Cr2+. The acetic acid ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…Harris et al [16] reported that the ternary Ni-Fe-Cr alloys containing 8%Cr was electrodeposited from an aqueous solution containing acetic acid. They found that the acetic acid served to limit the precipitation of nonmetallic material on the electrode by forming a soluble complex with Cr 3+ ions.…”
Section: +mentioning
confidence: 99%
“…Harris et al [16] reported that the ternary Ni-Fe-Cr alloys containing 8%Cr was electrodeposited from an aqueous solution containing acetic acid. They found that the acetic acid served to limit the precipitation of nonmetallic material on the electrode by forming a soluble complex with Cr 3+ ions.…”
Section: +mentioning
confidence: 99%
“…It was known that the addition of molybdenum to the deposits enhances the resistivity, but reduces the MR effect, which decreases to zero value at 4% Mo [12]. Chromium alloying has a smaller effect in decreasing MR up to 6% Cr [11]. In this work, we study the effect of the addition of both Cr and Mo to Permalloy films.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, it has became of an interest to investigate the deposition of the films from various solutions containing different metal ions as well as different complexing compounds for realization of the multi-elements alloy systems [10]. It has been reported that the addition of chromium to Permalloy caused a decrease in saturation induction (B s ) and anisotropy field (H k ) [11]. Also the electrical resistivity was one of the most important properties for soft magnetic films to be able to reach a good performance at high frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The need for alternative surface coatings to replace conventional Cr coating from toxic hexavalent Cr baths has attracted great attention in recent years (Harris et al, 1995;McDougall et al, 1998;Song and Chin, 2002). Thus instead of using only Cr coating, Cr-Ni alloy coating has been applied on steel by thermal spray techniques and studies have been carried out on its hot corrosion behavior at 400 0 C in air and in air containing SO 3 (Ou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%